Tendencias de investigación en branding enfocadas al adulto mayor: Análisis bibliométrico y revisión sistemática de la literatura; Trends in branding research focused on the elderly - Campo Elías López Rodríguez; Marithza Cecilia Sandoval Escobar (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The purpose of this article is to identify research trends in branding and brand building focused on the elderly, considering the importance of knowledge of this consumer segment, based on the sociodemographic changes corresponding to the population structure in the world. For this purpose, a bibliometric analysis was carried out using the Scopus database and developed with the R Core Team 2020 -Bibliometrix software, followed by a qualitative systematic review of the PRISMA type. The results show that there is a recent interest in research on the study of branding and related topics of consumer analysis of the elderly segment, although it still has a low level of scientific production. The findings identify as the most relevant topics those associated with brand equity, brand image, market orientation, relationship marketing strategies, market segmentation, and senior consumer behavior. Regarding brand image, the most characteristic aspects of the studies are related to age psychographics, cognitive processes, self-confidence and boldness. From the previous review, it is recognized the relevance of making greater research efforts to respond to the need for knowledge about the behavior of the older adult consumer, since there are few studies that allow identifying the influences, processes and behavioral patterns of this market segment in the world.
Keywords: M31; M70; 330; branding; bibliometrics; brand image; brand equity; consumer; olderadults